Pengaruh kinerja keuangan terhadap linkage non multifinance - Shihab Iqbal; Deasy Tantriana (Faculty of Economics, Universitas Islam Indonesia, 2018)
This study aims to determine the effect of NPF and profit-sharing ratio of linkage financing to non-multi-finance linkage at Bank BNI Syariah. The research method used in this study is a quantitative approach with the type of associative research. The result of this research shows that there are simultaneous effects of NPF and profit-sharing ratio on non-multi-finance linkage. It is also known that the partial correlation between NPF and non-multi-finance linkages shows a significant influence. Likewise, the partial correlation between profit-sharing ratio and non-multi-finance linkages shows a significant influence. Based on the result of this study, profit-sharing ratio is more dominant in influencing non-multi-finance linkage. The conclusion of this study is that NPF and profit-sharing ratio are important factors in policy-making of approving a non-multi-finance linkage financing. Therefore, it is necessary to pay close attention to the state of NPF and Profit-Sharing Ratio, thus there will be no error in making decisions regarding non-multi-finance linkage financing.